Development Of Student Worksheets Based On Discovery Learning - Diah, Istining; Sitorus, Masganti; Siregar, Tanti Jumaisyaroh (Yana Research, 2022)
This research is a development research that refers to the 4-D model, namely Define, (defining), Design (design), Develop (development), Disseminate (dissemination). The subjects of this study were students of class X SMA Swasta Rakyat Pancur Batu, totaling 17 students. The instruments used to measure the quality of the student worksheets that were developed were media assessment sheets by expert lecturers and mathematics teachers to measure the validity, and student response questionnaires. The quality of the validity of the learning media meets the valid criteria based on the average score of the media assessment sheet, which is 3.68 with a good category. Product validity by material expert lecturers is 4.0 with good category. And the practicality of the student response questionnaire is 4.1 with a good category. These findings indicate that the development is valid and feasible to use for SPLTV learning in class X SMA Swasta Rakyat Pancur Batu.